The quick-reference guide to counseling women - Clinton, Timothy E., 1960-; Langberg, Diane (Grand Rapids, MI. : Baker Books, 2011)
Women have unique needs and unique problems that require understanding, empathy, and direction from their pastors and counselors. For anyone who is called to counsel women, The Quick-Reference Guide to Counseling Women will be a welcome guide to bring hope, life, and freedom to women in need. This A-Z guide gives pastors, professional counselors, and lay helpers the information they need to help female church members, clients, and friends work through their spiritual and emotional issues. The many topics addressed include:healthy relationships conflict and stress sexuality, pregnancy, and infertility emotional and physical abuse roles of women. Each of the forty topics covered follows a helpful eight-part outline and identifies typical symptoms and patterns, definitions and key thoughts, questions to ask, directions for the conversation, action steps, biblical insights, prayer starters, and recommended resources.
Abortion -- Aging -- Anger -- Birth control -- Cancer -- Child sexual abuse -- Chronic pain -- Codependency and relationship addiction -- Depression -- Diet and nutrition -- Divorce -- Drug and alcohol addiction -- Eating disorders -- Emotional abuse -- Envy and jealousy -- Fear and anxiety -- Forgiveness -- Gossip -- Grief and loss -- Infertility -- Lesbianism and same-sex attraction -- Masturbation -- Menopause -- Miscarriage -- Obesity -- Physical abuse -- Pregnancy -- Prostitution -- Rape -- Relationships with men -- Relationship with Christ -- Roles of women -- Self-worth and approval -- Sex addiction -- Sexual desire and expectations -- Sexual harassment -- Sexually transmitted diseases -- Singleness -- Single parenting -- Strength in conflict and stress -- Final thoughts: helping women in crisis.
Includes bibliographical references.
Keywords: Women -- Pastoral counseling of; Church work with women